Technology adoption of automated vendor management system in Company Z through technology assessment and scenario planning - Bordeos, Eliza R.; Imbang, Glen (Quezon City University of the Philippines Diliman, 2017)
The study focuses on the Vendor Management System (VMS) of Company Z. Company Z is a utility company serving 6 million people in Metro Manila. The goal of the company is to become a leader in its industry. This comes with support with the national development and environmental sustainability. Vendor management is under the Supply Chain Management (SCM). SCM is responsible in supply of goods and services to support the overall operations of the company. It has four departments namely, Procurement, Logistics, Warehousing and Vendor Management. Procurement department is the team who handles the purchases of the goods and services of the company. Logistics is the one that delivers or mobilizes the goods and services to warehouses and customers. Warehousing generates stock status, monitors delivery, and manages the warehouse of materials of the company. Vendor management is responsible for accreditation, data analytics, monitors vendor performance and risk assessment of vendors that supports the needs of the company.
The status of vendor management of Company Z is a mixed manual and in-house developed tools. These tools such as SharePoint for performance evaluation and Air table for vendor database are not integrated to SAP where the details of the project were encoded after conducting procurement processes offline. There are difficulties and challenges in using these tools. The reliability, time capture and generation of reports are tedious. No monitoring of spend, no visibility of vendor performance, strategic approach in procurement is weak and vendor database is inefficient. This leads to vendor heavy workload, poor quality of work and vendor delays in deliverables. Due to this, procurement team was also affected and adds delays on procurement process and heavy workload which constitutes to manpower turnover. Due to this VMS automation can be adopted to solve these problems.
Based from the study of Limberakis (2012), 47 percent of the companies in a global stand point believe in the importance of VMS in their companies. Best in class is generating an average of 12 percent savings from implementation.
To further determine the capacity and technology status of Company Z, a survey is conducted. It was found that users perceived automated VMS as useful to their daily task, however, they presumed that it is not user friendly. Also, based from the technology assessment, Company Z is found higher in the average. The top management uses technology as business strategy with prudent approval procedures.
There are several VMS providers available in the market. To be able to magnify what VMS can do to a firm, there are three technology providers identified to further determine their functionalities and benefits to organizations. On a global technology scanning, supply chain has already reached its digital form. The new trends with vendor management includes collaboration in product development, idea innovation/crowdsourcing, advanced sourcing analytics and social listening.
Based from the variables generated from the scenario planning, the clusters that gained the most impact are the top management, cost component, external innovative culture, human capital and political/governance. The variable that are most uncertain are economic force and environmental clusters.
There are three scenarios that build from these clusters. Scenario one is the top management realized the need of VMS automation to Company Z. In scenario two, VMS automation will become a competitive advantage of Company Z against its rivals. And the third scenario is that the pool of vendors will be changed and Company Z will be the "customer of chocei". The best scenario formulated is the one that provides significant impact to the company.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Management information systems -- Automation; Strategic planning; Technology -- Risk assessment